2021
DOI: 10.24996/ijs.2021.62.6.36
|View full text |Cite
|
Sign up to set email alerts
|

Irregular urban Expansion and Its Effects on Air Temperature over Baghdad City using Remote Sensing Technique

Abstract: Heat island is known as the increases in air temperature through large and industrial cities compared to surrounding rural areas. In this study, remote sensing technology is used to monitor and track thermal variations within the city center of Baghdad through Landsat satellite images and for the period from 2000 to 2015. Several processors and treatments were applied on these images using GIS 10.6 and ERDAS 2014, such as image correction and extraction, supervised classification, and selection of training sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…GIS is an effective tool in planning and designing where it is considered as a new and developing system in environmental data management and in making appropriate decisions. Geographic information system (GIS) consider as a significant software that cannot be separated from remote sensing techniques [14], where GIS techniques is collecting, submitting, and analyzing spatial data in an accurate and effective method [15]. At the moment, remote sensing and GIS are providing cutting-edge technologies for sophisticated environment management [16].…”
Section: Resultsmentioning
confidence: 99%
“…GIS is an effective tool in planning and designing where it is considered as a new and developing system in environmental data management and in making appropriate decisions. Geographic information system (GIS) consider as a significant software that cannot be separated from remote sensing techniques [14], where GIS techniques is collecting, submitting, and analyzing spatial data in an accurate and effective method [15]. At the moment, remote sensing and GIS are providing cutting-edge technologies for sophisticated environment management [16].…”
Section: Resultsmentioning
confidence: 99%
“…Baghdad city is considered as an urban area with clear human activities, especially at city Centre, see figure 1. After 2003, the number of vehicles entering the streets of Baghdad increased, and the number of generators installed increased due to the lack of central electricity generation, [13] this was accompanied by an overflow on agricultural land, which led to the conversion of large areas of agricultural land to residential land, which could be accompanied by changes in the appearance of thermal islands within the city. Location Study at now, deal with all Baghdad province, and will be concentrated on one grid station inside Baghdad city Centre (33.35°N, 44.35°E) to study the vertical profile up to 5000 meter, see figure 2.…”
Section: Locationmentioning
confidence: 99%
“…They demonstrated that at a distance of 20 m, the inlet air temperature approaches the soil temperature, and the COP and Q decreased with increasing inlet air temperature but increased with increasing pipe length. Literature also reported data for the EXH at different design configurations (Jakhar et al, 2015;Jakhar et al, 2016;Hassoon and Ali, 2021). Rouag et al (2018) studied the thermal design of an EXH using a new developed semi-analytical method with soil temperature distribution in hot and dry climates.…”
Section: Introductionmentioning
confidence: 99%